2010
DOI: 10.1016/j.watres.2010.07.061
|View full text |Cite
|
Sign up to set email alerts
|

Development of microbial and chemical MST tools to identify the origin of the faecal pollution in bathing and shellfish harvesting waters in France

Abstract: The microbiological quality of coastal or river waters can be affected by faecal pollution from human or animal sources. An efficient MST (Microbial Source Tracking) toolbox consisting of several host-specific markers would therefore be valuable for identifying the origin of the faecal pollution in the environment and thus for effective resource management and remediation. In this multidisciplinary study, after having tested some MST markers on faecal samples, we compared a selection of 17 parameters correspon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
69
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 47 publications
5
69
1
Order By: Relevance
“…Our findings agree with (Gourmelon et al, 2010;Liang et al, 2015; as this tool can accurately simulate the distribution of site-related environmental parameters. Based on the weight of the variables, the study clearly revealed that production period and oyster culture technique type were significantly associated with microbiological quality.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Our findings agree with (Gourmelon et al, 2010;Liang et al, 2015; as this tool can accurately simulate the distribution of site-related environmental parameters. Based on the weight of the variables, the study clearly revealed that production period and oyster culture technique type were significantly associated with microbiological quality.…”
Section: Resultssupporting
confidence: 87%
“…Lantern nets should be used in deep water locations where strong currents are rare (Yang et al, 2006) and water renewal in these places is poor, especially in relation with contamination sources that may interfere with the sanitary quality of these animals. So legislation should also take into account several parameters like biological, chemical and physical parameters (Gourmelon et al, 2010;Santos et al, 2011;Silva et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From 2011, the revised European Bathing Water Directive (7) additionally requires bathing water profiles to be established and the identification of any pollution sources, to ensure efficient water quality management. Over the last decade, a panel of host-associated markers, known as microbial source tracking (MST) markers, has been derived from enteric bacteria or viruses or from chemical products (3,10,35). Criteria required for an MST marker to be useful and reliable, and thus relevant for inclusion in an operational toolbox, include (i) high sensitivity and specificity to the targeted species, independent of geographic region, and (ii) the potential to offer a credible evidence-based description of the fecal loading in environmental waters that do not comply with quality standards (13).…”
mentioning
confidence: 99%
“…porcinum has been proposed as an MST marker for animal species (35). Some of these Bifidobacterium markers have been successfully applied in Europe and some parts of the United States (2,8,14,21,26,38).…”
mentioning
confidence: 99%